2019
DOI: 10.30636/jbpa.21.35
|View full text |Cite
|
Sign up to set email alerts
|

Are public managers more risk averse? Framing effects and status quo bias across the sectors

Abstract: Modern reforms meant to incentivize public managers to be more innovative and accepting of risk are often implicitly based in the longstanding assumption that public employees are more risk averse than their private sector counterparts. We argue, however, that there is more to learn about the degree to which public and private managers differ in terms of risk aversion.  In order to address this gap, we field a series of previously validated experiments designed to assess framing effects and status quo bias in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…When making judgements about what is best for the community (Yang and Callahan, 2007), public managers are typically confronted with risk and uncertainty (Nicholson-Crotty et al, 2019). As already mentioned, in most cases, they face "risk-risk trade-offs" (Hood, 2002, p. 32) rather than a simple choice between risk and its absence (Hood, 2002(Hood, , 2007.…”
Section: Psm and Risk Propensitymentioning
confidence: 99%
See 3 more Smart Citations
“…When making judgements about what is best for the community (Yang and Callahan, 2007), public managers are typically confronted with risk and uncertainty (Nicholson-Crotty et al, 2019). As already mentioned, in most cases, they face "risk-risk trade-offs" (Hood, 2002, p. 32) rather than a simple choice between risk and its absence (Hood, 2002(Hood, , 2007.…”
Section: Psm and Risk Propensitymentioning
confidence: 99%
“…With respect to the public sector context, scholars typically have argued that public agents are more risk-averse than their private counterparts (Bellante and Link, 1981;Buurman et al, 2012;Guiso and Paiella, 2008;Hartog et al, 2003;Pfeifer, 2010). Nevertheless, Bozeman and Kingsley (1998) and Nicholson-Crotty et al (2019) found only small differences in risk aversion across sectors. However, based on the concept of PSM, public servants' willingness to serve others and to realize the opportunity to act in the interests of those others should motivate them to take (additional) risks, when they have high levels of PSM.…”
Section: Psm and Risk Propensitymentioning
confidence: 99%
See 2 more Smart Citations
“…10 Leadership, cooperation, empathy-these are all areas with which the policy and public administration fields have concerned themselves, yet these lines of research have largely remained separate. Further, most of the work (though certainly not all-see Nicholson-Crotty, Nicholson-Crotty, and Webeck 11 and Christensen and Wright 12 for two recent examples) has focused on the public's attitudes surrounding policy and bureaucracy. The present article endeavors to demonstrate how we might take the existing momentum forward by tackling theories of bureaucratic behavior.…”
mentioning
confidence: 99%